Sacred and Profane in Chaucer and Late Medieval Literature : Essays in Honour of John V. Fleming - Robins, William Randolph, 1964-; Epstein, Robert W. (Robert William), 1964-; Fleming, John V. (Book collections on Project MUSE., 2010)
"Literary depictions of the sacred and the secular from the Middle Ages are representative of the era's widely held cultural understandings related to religion and the nature of lived experience. Using late Medieval English literature, including some of Chaucer's writings, these essays do not try to define a secular realm distinct and separate from the divine or religious, but instead analyze intersections of the sacred and the profane, suggesting that these two categories are mutually constitutive rather than antithetical.